DEVELOPMENT OF PRODUCT PACKAGING AS BRAND IDENTITY IN THE JIHAN CAKE AND COOKIES BUSINESS IN MAKASSAR CITY - Ulil Azmi Asmin; Syamsu Alam, Asmayanti (CV. Adiba Aisha Amira, 2025)
The development of MSMEs in the culinary field continues to experience growth. The simplest packaging is a container used to wrap and protect the product. In facing the tight competition in the culinary business, a strategy is needed so that a business can be recognized and remembered by consumers. One of them is to develop packaging to serve as a marketing medium through designs that showcase brand identity, thereby differentiating it from similar businesses. This research aims to create packaging designs for Jihan Cake and Cookies to enhance brand identity. The development method used is the Design Thinking method with five stages: Empathize, Define, Ideate, Prototype, and Test. The empathy stage involved field observations to identify the existing problems, the define stage involved information gathering and problem identification, and clearly defining the scope of the problem. The ideation stage involved critical, creative, and innovative thinking. The prototype stage involved printing three alternative packages to be shown to customers, and the test stage involved giving questionnaires to consumers to see which package design received the most votes and to assess the feasibility of the packaging. The results of the product feasibility testing show that the packaging of Jihan Cake and Cookies is very feasible with a high percentage of 88.5%. Based on the packaging selection results, the first packaging design received the most votes, and the owner has also agreed to use it. Thus, it can be concluded that the product packaging can serve as a marketing medium by displaying the logo, colors, and shape, thereby creating a brand identity in the physical aspects of the packaging to make it easily recognizable and memorable to consumers, distinguishing it from competitors.